Assessment of medication adherence and factors affecting it among diagnosed hypertensive patients attending outpatient department in some selected hospitals in Zaria metropolis - Ladan, Muhammad Awwal; Musa, Halima Abdul; Sani, Dalhat Khalid; Agbim, Evleyn E.; Aliyu, A.; Lawal, Bilkisu Kankia (Nursing and Midwifery Council of Nigeria, 2016)
Background: Medication adherence ameliorates/reduces the complications associated with various disease conditions especially diseases that are not curable but rather, are to be managed from its onset to the end of its victim’s life, as seen in hypertensive patients. Adherence to medication is important for blood pressure control, but poor adherence is common. The objective of the study was to assess medication adherence, factors affecting it and the possible relationship.